Sistem Informasi Geografis pada Kasus Demam Berdarah Dengue di Kabupaten Kediri Tahun 2019 - Rochma Ashifa Affayani (Universitas Airlangga, 2023)
Background: Prevention of the spread of disease needs to be through various steps, one of which is to know the potential for the spread of the disease in question. One of the dangerous diseases that still occurs in high numbers in Indonesia is dengue hemorrhagic fever (DHF). There are still various deficiencies in DHF control, including an information guide system regarding DHF cases that has not been effective and has not accurately represented the distribution of DHF in various regions. In an effort to obtain geographic information related to the distribution of DHF cases, information technology can be utilized, namely the Geographic Information System (GIS). Objectives: To utilize the Geographic Information System in describing the distribution of Dengue Hemorrhagic Fever (DHF) case data and analyzing the factors that influence the number of DHF cases in Kediri Regency in 2019. Methods: This study used a quantitative method with a cross sectional design. The research population includes all sub-districts in Kediri Regency in 2019, namely 26 sub-districts. The research sample used the entire available population. The data source used comes from secondary data, namely in the form of a map of Kediri Regency and the Health Profile of Kediri Regency in 2019. Results: The results of further testing related to the relationship between population density and the number of DHF cases did not have a significant effect with a p-value of 0.69076, the distribution variable for the percentage of drinking water facilities that met the requirements did not have a significant effect on the number of DHF cases with a p-value of 0.90729, the variable distribution of the number of public places meeting health requirements has no significant effect on the number of DHF cases with a p-value of 0.54618, and the variable distribution of the number of families with access to healthy latrines has a significant effect on the number of DHF cases with a p-value of 0.00013 . Conclusion: The population density variable, the distribution variable for the percentage of drinking water facilities that meet the requirements, and the distribution variable for the number of public places meeting health requirements have no significant effect on the number of DHF cases that occur in Kediri Regency in 2019. Meanwhile, the variable distribution of the number of families with access to healthy latrines has a significant effect on the number of DHF cases in Kediri Regency in 2019.